Evaluation of job satisfaction of Physical Education Teachers - Krapp do Nascimento, Raquel (2019)
The paper aimed to analyze job satisfaction, taking into consideration the personal characteristics (sex, age, and marital status) of 73 Physical Education coaches from São José (SC). Data was collected using a sociodemographic questionnaire and the Evaluation Scale of Quality of Life at Work Perceived by Physical Education Teachers and analyzed using the Mann-Whitney U-Test. Results revealed a significant difference in the overall evaluation of job satisfaction only for the age group (31 years of age or older>up to 30 years of age). Working conditions differed according to gender (women>men) and age (31 years of age or older>up to 30 years of age), while career progression, autonomy at work, and social relevance differed in relation to teachers’ age (31 years of age or older>up to 30 years of age). It was concluded that women were more satisfied with their working conditions than men, while younger teachers were more dissatisfied in both overall assessment and in most dimensions compared to older teachers.